2010
DOI: 10.1126/science.1187988
|View full text |Cite
|
Sign up to set email alerts
|

Normal Modes and Density of States of Disordered Colloidal Solids

Abstract: The normal modes and the density of states (DOS) of any material provide a basis for understanding its thermal and mechanical transport properties. In perfect crystals, normal modes are plane waves, but they can be complex in disordered systems. We have experimentally measured normal modes and the DOS in a disordered colloidal crystal. The DOS shows Debye-like behavior at low energies and an excess of modes, or Boson peak, at higher energies. The normal modes take the form of plane waves hybridized with locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
150
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(161 citation statements)
references
References 30 publications
11
150
0
Order By: Relevance
“…20 it was observed that contact-opening excitations in packings are marginally stable, so that the bounds 14 and 15 are satisfied with equality, with numerical values γ ≈ 0:4, θ ℓ ≈ 0:17, and θ e ≈ 0:44. Saturation of [15] was recently proven for certain dynamics (38). Assuming such marginal stability, it follows that θ f = θ ℓ < θ e and the exponent θ e can be determined from θ e = 2θ f =ð1 − θ f Þ ≈ 0:41, a value consistent with the direct measurement 0.44.…”
Section: Hard Spheressupporting
confidence: 60%
See 1 more Smart Citation
“…20 it was observed that contact-opening excitations in packings are marginally stable, so that the bounds 14 and 15 are satisfied with equality, with numerical values γ ≈ 0:4, θ ℓ ≈ 0:17, and θ e ≈ 0:44. Saturation of [15] was recently proven for certain dynamics (38). Assuming such marginal stability, it follows that θ f = θ ℓ < θ e and the exponent θ e can be determined from θ e = 2θ f =ð1 − θ f Þ ≈ 0:41, a value consistent with the direct measurement 0.44.…”
Section: Hard Spheressupporting
confidence: 60%
“…These two sets of results yield a stability constraint on the microscopic structure of hard-sphere glasses, which in practice appears to lie very close to saturation (6,7,12). Such marginal stability implies the abundance of very soft elastic modes, as confirmed empirically (6,7,(12)(13)(14)(15)(16), and fixes the scaling behavior of elasticity as jamming is approached (7). In particular the particles' mean-squared displacement was predicted to follow hδR 2 i ∼ ðϕ c − ϕÞ κ with κ = 1:5 (7) instead of the naive κ = 2, which would hold in a crystal: Particles in the glass fluctuate much more than the size of their cage (defined as the typical distance between particles), due to the presence of collective soft modes.…”
mentioning
confidence: 92%
“…The work is made possible by recently developed covariance matrix techniques that have led to the measurement of vibrational modes in thermal colloids from microscopy experiments [9][10][11]. The colloidal glasses are composed of thermosensitive microgel particles which readily permit in situ variation of the sample packing fraction.…”
Section: Recommended Citationmentioning
confidence: 99%
“…The measured displacement covariance matrix [9][10][11]19] was employed to extract vibrational modes of the shadow colloidal system, which shares the same geometric configuration and interactions of the experimental colloidal system, but is undamped. A displacement covariance matrix is constructed by calculating the equal-time covariance of displacements between each particle pair for each direction.…”
Section: Recommended Citationmentioning
confidence: 99%
“…However, instead of a pure drop of g(ω) at higher frequencies, a typical "boson peak" can develop in disordered systems [39], the origin of which is still under debate [40]. In our example of a two-dimensional disordered solid, the curve for g(ω) in Fig.…”
Section: Figmentioning
confidence: 99%